2021
DOI: 10.1177/1077559520987302
|View full text |Cite
|
Sign up to set email alerts
|

Association of State-Level Earned Income Tax Credits With Rates of Reported Child Maltreatment, 2004–2017

Abstract: Poverty is an important predictor of child maltreatment. Social policies that strengthen the economic security of low-income families, such as the Earned Income Tax Credit (EITC), may reduce child maltreatment by impeding the pathways through which poverty leads to it. We used variations in the presence and generosity of supplementary EITCs offered at the state level and administrative child maltreatment data from the National Child Abuse and Neglect Data System (NCANDS) to examine the effect of EITC policies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 47 publications
3
40
0
Order By: Relevance
“…This pattern would be consistent with the hypothesis that the substantial loss in income from the end of the PUC program may have led to an increase in child abuse; this would be valuable to examine in future research. These findings are consistent with previous literature linking decreased family income downstream of policy changes to increased reports to Child Protective Services [ 25 - 27 ]. Child-witnessed IPV searches, but not exposure to IPV searches, increased at the time of SIP policies.…”
Section: Discussionsupporting
confidence: 92%
“…This pattern would be consistent with the hypothesis that the substantial loss in income from the end of the PUC program may have led to an increase in child abuse; this would be valuable to examine in future research. These findings are consistent with previous literature linking decreased family income downstream of policy changes to increased reports to Child Protective Services [ 25 - 27 ]. Child-witnessed IPV searches, but not exposure to IPV searches, increased at the time of SIP policies.…”
Section: Discussionsupporting
confidence: 92%
“…28 In addition, the Earned Income Tax Credit has been associated with decreases in hospital admissions for pediatric abusive head trauma, reports of child neglect, and foster care entries and improvement in short-term Behavioral Problem Index scores. [29][30][31][32] Other studies have found cash transfers such as a onetime deposit into 529 college savings accounts at birth are associated with improved maternal mental health, child social-emotional development, and parental educational expectations, with low-income families experiencing larger benefits. 25 To facilitate the uptake of financial services with the goal of improving child health and development outcomes, embedded financial services need to offer guardians consistent, holistic support.…”
Section: Discussionmentioning
confidence: 99%
“…EITC benefits have previously been associated with reductions in selfreported child welfare involvement, 17 reports for neglect (but not abuse), 46 and foster care entry. 15,16 Klevens et al 31 reported a marginally significant effect for EITC reducing abusive head trauma.…”
Section: Figurementioning
confidence: 99%